ROS-inducing potential, influence of different porogens and in vitro degradation of poly (D,L-lactide-co-glycolide)-based material (eXPRESS Polymer Letters)
Porous, poly(D,L-lactide-co-glycolide) (PLGA) materials were prepared by physicochemical solvent/non-solvent method with polyvinyl pyrrolidone (PVP) as a stabilizer and with silicone oil, paraffin, hydrogen peroxide or sodium chloride as a porogen. The obtained PLGA particles without porogens are non-agglomerated, uniform and with particle size on the submicron scale. The formation of intracellular reactive oxygen species (ROS) was measured spectrophotometrically using a fluorescent probe, 2,7-dichlorofluorescein diacetate (DCFH-DA) and it is shown that PLGA nanospheres are not inducers of intracellular formation. Porous PLGA scaffolds obtained in the experiment with sodium chloride as porogen and water as solvent of the porogen had apparently uniform pore morphology with spheroidal pore in shape and well controlled three-dimensional interconnected network. PLGA scaffolds are highly porous with similar porosity values. The degradation of PLGA nanoparticles and PLGA porous materials were studied in phosphate buffered saline as a degradation medium. The samples were characterized by Infrared Spectroscopy (IR), X-ray difractometry, Zeta potential measurements, Scanning Electron Microscopy (SEM) and Ultraviolet Spectroscopy (UV).